FLUOR LEVEL IN WATER AND FLUOROSIS IN 6 TO 12 YEARS OLD CHILDREN, QUITO, ECUADOR - Arroyo Bonilla, David Alejandro (2016)
Objectives: Our aim was to determine the prevalence of fluorosis among the population of children who live in Tumbaco Valley, Quito, Ecuador. We sought to establish its relation to the concentration of fluoride in the water supply of this área. Material and methods: The sample was 62 children who were selected based upon previously defined inclusion and exclusion criteria. All of the children were clinically examined; a photographic record of upper anterior teeth surfaces was performed. Results: The analyzed data showed that only 23,3% of the children surveyed had rates of dental fluorosis, with TF-2 being the most common. Chemical analysis of water from the supply source showed the presence of fluoride in very small amounts which did not exceed 0,32 mg/L. Conclusions: The low presence of fluoride in the examined water sources explains the absence of fluorosis in the assessed population. This is evidence that the strategies set forth by health authorities to decrease the amount of f